2012
DOI: 10.1088/0957-4484/23/28/285601
|View full text |Cite
|
Sign up to set email alerts
|

Growth of InAs/InP core–shell nanowires with various pure crystal structures

Abstract: We have studied the epitaxial growth of an InP shell on various pure InAs core nanowire crystal structures by metal-organic vapor phase epitaxy. The InP shell is grown on wurtzite (WZ), zinc-blende (ZB), and {111}- and {110}-type faceted ZB twin-plane superlattice (TSL) structures by tuning the InP shell growth parameters and controlling the shell thickness. The growth results, particularly on the WZ nanowires, show that homogeneous InP shell growth is promoted at relatively high temperatures (∼500 °C), but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 30 publications
4
59
0
Order By: Relevance
“…It has also been demonstrated that radial growth can be tuned to be selective to certain nanowire facets. [18][19][20] Controlling the crystal structure of different segments of the nanowire, and thereby, changing the surface energies of the segments formed along the axis would provide ideal templates for studying selective radial growth. In a number of studies it has been observed that the rate of radial growth strongly depends on the crystal phase of the nanowires, 17 attributed to their different surface energies.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that radial growth can be tuned to be selective to certain nanowire facets. [18][19][20] Controlling the crystal structure of different segments of the nanowire, and thereby, changing the surface energies of the segments formed along the axis would provide ideal templates for studying selective radial growth. In a number of studies it has been observed that the rate of radial growth strongly depends on the crystal phase of the nanowires, 17 attributed to their different surface energies.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of controlling and improving semiconducting nanowire (NW) devices for various applications1234567, an extensive research effort has been invested in studying NW growth; this was typically achieved by studying the different effects of user controlled parameters: (i) materials - including type and size of NW catalyst, the growth substrates and precursors, and (ii) by altering growth-system parameters, i.e., temperature and precursor flow891011121314151617. In the following report we present a new paradigm, that of catalyst shape engineering, as a useful tool to control NW growth results; in particular, we show that by imposing a non-hemispherical shape to the catalyst-substrate interface, anisotropic cross-sectioned NWs may be grown - NWs with potentially new physical characteristics.…”
mentioning
confidence: 99%
“…This considerable difference is due to two reasons. First, the equivalent facet orientation of nanowires in the ZB phase itself is different from (100), and they generally grow slower than (100) facets under the considered growth conditions (for example {110} and {112} face growth rate of the side facets of nanowires in WZ phase is inherently even lower than th equivalent, 44,52 making the actual thickness much lower than expected. However, the growth rate of the QWs seems to remain constant thickness with growth time.…”
Section: Experimental Methodsmentioning
confidence: 99%